Rancang Bangun Media Edukasi 3D Interaktif Pembelajaran IPA Berbasis Mobile - Suharjanto Utomo; Samsul Budiarto; Iswanto; Hernawati; Raihan Fajar Sidik (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid development of digital technology provides new opportunities to improve the quality of learning, particularly in science education. Conventional learning media such as textbooks and static images are considered less effective in conveying concepts that are highly visual and abstract. This study aims to design and develop an interactive 3D mobile-based educational media as a learning tool for science subjects, with a case study on the human digestive system at SMP Muhammadiyah 5 Cimahi. The application enables students to explore the digestive system organs through interactive 3D models supported by audio narration and explanatory texts. The development method employed is the Multimedia Development Life Cycle (MDLC), which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. The application was evaluated through alpha testing using the blackbox method and beta testing by distributing questionnaires to teachers and 14 eighth-grade students. The evaluation results indicate that the application is well-accepted and contributes positively to students’ understanding of the human digestive system. The questionnaire results showed a score of 4.37, indicating that the application is engaging, easy to use, and interactive. These findings highlight the potential of interactive 3D mobile-based educational media as an innovative alternative for more engaging and effective science learning.